Health care administration : planning, implementing, and managing organized delivery systems / edited by Lawrence F. Wolper. - Wolper, Lawrence F. (Jones and Bartlett Publishers, 2004)
Provides comprehensive coverage of detailed functional, technical, and organizational matters that pertain to organized delivery systems. It also extensively covers matters that relate to hospitals and functions that occur at the hospital level. With revisions that reflect the emerging issues in health care, this classic text is a must-have for both health administration students and professionals.